Association Between Recombinant Growth Hormone Therapy and All-Cause Mortality and Cancer Risk in Childhood: Systematic Review and Meta-Analysis - Mengyang He; Xiangling Deng; Xuan Wang; Yuxiang Wan; Jinchang Huang; Zhixin Zhang; Wenquan Niu (Frontiers Media S.A., 2022)
ObjectivesThe safety of recombinant human growth hormone (rhGH) treatment in childhood and the role of rhGH therapy in promoting tumorigenesis and progression have been the subject of debate for decades. We aimed to systematically assess the relationship between rhGH therapy in children and adolescents and clinical outcomes, including all-cause mortality, cancer mortality, cancer incidence, and risk of the second neoplasm.MethodsLiterature retrieval, study selection, and data extraction were completed independently and in duplicate. Effect-size estimates are expressed as standardized mortality ratios (SMRs), standardized incidence ratio (SIR), and relative risk (RR) with a 95% CI.ResultsData from 24 articles, involving 254,776 persons, were meta-analyzed. Overall analyses revealed the association of rhGH therapy was not statistically significant with all-cause mortality (SMR = 1.28; 95% CI: 0.58-2.84; P = 0.547; I2 = 99.2%; Tau2 = 2.154) and cancer mortality (SMR = 2.59; 95% CI: 0.55-12.09; P = 0.228; I2 = 96.7%; Tau2 = 2.361) and also cancer incidence (SIR = 1.54; 95% CI: 0.68-3.47; P = 0.229; I2 = 97.5%; Tau2 = 2.287), yet statistical significance was observed for second neoplasm (RR = 1.77; 95% CI: 1.33-2.35; P = 0.001; I2 = 26.7%; Tau2 = 0.055). Differences in the geographic region, gender, treatment duration, mean rhGH dose, overall rhGH exposure dose, and initial disease accounted for heterogeneity in the subgroup analyses.ConclusionOur findings indicate that the rhGH therapy is not related to all-cause mortality and cancer mortality and cancer incidence, yet it seems to trigger a second tumor risk. Future prospective studies are needed to confirm our findings and answer the more challenging question regarding the optimal dose of rhGH therapy in children and adolescents.